Legal Review Of The Position And Duties Of The Ethical Council In The Implementation Of Elections (Study on the Election Organizer Honorary Council) - Anggalana; Fathul Aziz (International Journal of Education, Vocational and Social Science, 2025)
The principle of honesty and fairness is the principle of elections which is integrated with the principles of direct, general, free and secret elections after the reforms. The addition of the principle of honesty and fairness as one of the principles in the implementation of democratic elections is not without reason. The principle of "honesty" implies that in the implementation of elections, every party related to the implementation of elections, including election organizers, government officials, election participants, election supervisors, election observers, and voters must behave and act honestly. Referring to the Election Law, the DKPP's decision is final and binding, and the KPU and BAWASLU must monitor its implementation in accordance with Bawaslu's responsibilities. DKPP decisions, functions and locations. The research method uses a normative and empirical juridical approach . The types of data used are secondary data and primary data. Data collection through library research and field research . The data analysis used is qualitative juridical. The results of the study show the position and duties of the Election Organizer Honorary Council as an institution that carries out a blending function between regulatory, administrative and punitive functions that are generally separated, but are appropriately carried out simultaneously by this new institution. Election organizers are treated as an ethics court. Legal settlement of violations of the code of ethics committed by the Election Organizer Honorary Council is final and binding, and the final decision after the DKPP decision comes into effect is decided and announced in the General DKPP General Assembly by providing legal remedies or other legal remedies, meaning nothing. That the decision is immediately binding and implemented. Therefore, all state and judicial administrators and DKPP decisions must be implemented correctly.